Code Switching in Discussion Activities in English Class - Novita Kusumaning Tyas (Universitas Hamzanwadi, 2020)
This study is aimed to find out the types and to explain the function of code switching which are produced in discussion activities in English class. Qualitative approach is used in this study. The result showed that the total number of code switching made by twelve students in discussion activities was 165 utterances. Based on grammatical classification, it was found 77 utterances or 46,67% for inter-sentential, 61 utterances or 36,97% for intra-sentential and 27 utterances or 16,36% for tag-switching. Based on contextual classification, it was found 106 utterances or 64,24% for situational and 59 utterances or 35, 76% for metaphorical. The function of code switching was often used by the students was emphasis the meaning of utterances. It holds 45 utterances or 27,27% from all utterances. Finally, it can be concluded that code switching cannot be avoided because basically they are not students who take English as their major so they lack of English and also code switching happened in order to make understandable meaning among them.